Pengenalan Media Pembelajaran Augmented Reality untuk Anak Berkebutuhan Khusus - Ferawati Ferawati; Detin Sofia; Petty Aprilia Sari (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2023)
The use of digital technology is the main factor in encouraging learning activities. Educators with expertise in the field can apply the principles of successful and efficient pedagogy when designing and implementing teaching strategies. Educators need increased capacity to strategize, organize, and produce open materials and face challenges when tasked with developing their own learning media. Children with special needs are those who have limited physical and psychological abilities. Therefore, the presence of versatile learning tools is significant. This activity aims to introduce Android-based learning media, namely augmented reality learning media, which is crucial in facilitating educational efforts for educators and students. Teachers and students of SKH YKDW 01 attended this service activity. The final results of the activities that have been carried out are proven by the enthusiasm of the participants after the end of the service activities and the questionnaire score of 61%, showing that students and teachers gave excellent scores to the augmented reality application.